Register to Buy and Sell Indonesian SEO Community on Telegram - 'Iffat, Umaimah; Layli Hamida; Jihan Fathinuriza Zain; Fariha Bibi (Jurnal Sastra Indonesia, 2025)
The rapid development of the internet has given birth to several influential platforms, such as social media. The increasing use of social media triggers the use of a particular community's distinctive language that reflects its culture. This study analyzes the buying and selling registers, functions, norms, and values of the Indonesian SEO Community (KSI). This qualitative research uses research in the form of a selling' feature (chat) sourced from the KS I Telegram group. The data was collected through participant observation, semi-structured interviews, and field notes. The analysis process occurs in the register, morphology, and function analysis stages. Using the theory of the formation of the wordKridalaksana (1992) and Yule (2010), it was found that the KSI register was mainly in the form of basic morphemes or did not undergo the formation process. Other formation processes are abbreviation, the merger of two non-predictive words (phrases), affixation or derivation, compounding (merging), and coinage (combination). Meanwhile, the function of using registers analyzed using the Thurlow & Brown framework (2003) is dominated by SEO terminology. Other registers also function for communication efficiency, persuasiveness, greetings, pronouns, informativeness, and transactions. A significant finding in this study is that instant messaging has a different context of use and pressure than other digital media. This is reflected in checkout registers that function as promotional closures and have lower pressure on buyers than TikTok live broadcasts. In addition, using neutral terms such as agan, colleague, guys, everyone, all, and mbah reflects inclusive and egalitarian community management. Through register analysis from the perspective of Digital Ethnography, the implications of this research can be used by business people to maximize their sales in the digital space.